2021
DOI: 10.21203/rs.3.rs-130595/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meaningful Activities During COVID-19 and Association With Mental Health in Belgian Adults.

Abstract: Background: The spread of COVID-19 has affected people’s daily lives and the lockdown may have led to a disruption of daily activities and a decrease of people’s mental health. Aim: To identify correlates of adults’ mental health during the COVID-19 lockdown in Belgium and to assess the role of meaningful activities in particular. Methods: A cross-sectional web survey for assessing mental health (General Health Questionnaire), resilience (Connor-Davidson Resilience Scale), meaning in activities (Engagement in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Mental health was also affected by disruption of daily activities due to lockdown. Cruyt et al (2021) identified a positive relation between lack of meaningful activities and reduced mental health among Belgian adults aged 18 years or older during COVID-19 restrictions. Leong Bin Abdullah, Murad.…”
Section: Introductionmentioning
confidence: 93%
“…Mental health was also affected by disruption of daily activities due to lockdown. Cruyt et al (2021) identified a positive relation between lack of meaningful activities and reduced mental health among Belgian adults aged 18 years or older during COVID-19 restrictions. Leong Bin Abdullah, Murad.…”
Section: Introductionmentioning
confidence: 93%